Using Thinking Routines To Improve The Reading And Writing Skills Of Elementary Students - Mala Rejeki Manurung; Siti Masitoh; Fajar Arianto (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2022)
Developing thinking skills in teaching and learning, including English lessons, is prominent. Reading and writing are the ability that requires synthesis and higherorder thinking skills. Thinking routines as part of thinking culture is one strategy to develop thinking skills. This study investigated the importance of thinking routines in improving sixth-grade elementary school students reading and writing skills. The quasi-experimental research was conducted with 64 students divided into a control group (N=32) and an experimental group (N=32). The topic of reading and writing was appropriate for the sixth-grade students’ developmental stage. Reading and writing tests were used as data collection tools. The experts validated the reading topic and the tests. The data is analyzed statistically using the Mann-Whitney U Test. The results reveal two significant findings. The first finding was that thinking routines did not significantly improve sixth-grade students’ reading skills. On the other hand, thinking routines improved writing skills significantly. The evidence from this study suggests using thinking routines in English teaching as a base to support and structure students thinking with various perspectives. In addition, thinking routines also support students in writing opinions based on the information given.